Rabbit Model of Extending Knee Joint Contracture: Progression of Joint Motion Restriction and Subsequent Joint Capsule Changes after Immobilization - Zhou, Yun; Zhang, Quan Bing; Zhong, Hua Zhang; Liu, Yi; Li, Jun; Lv, Hao; Jing, Jue Hua (The Journal of Knee Surgery, 2020)
This study aimed to develop a rabbit model of knee contracture in extension and investigate the natural history of motion loss and time-dependent changes in the joint capsule after immobilization. We immobilized the unilateral knee joints of 32 rabbits by maintaining the knee joint in a plaster cast at full extension. Eight rabbits were euthanized at 2, 4, 6, and 8 weeks after casting, respectively, and the lower extremities were disarticulated at the hip joint. Eight control group rabbits that did not undergo immobilization were also examined. We assessed the progression of joint contracture by measuring the joint range of motion, evaluating the histologic alteration of the capsule, and assessing the mRNA levels of transforming growth factor β1 (TGF-β1) in the anterior and posterior joint capsules. After 2 weeks of joint immobilization, the knee joint range of motion was limited, the synovial membrane of the suprapatellar and posterior joint capsules was thickened, the collagen deposition was increased, and the mRNA levels of TGF-β1 were elevated in the anterior and posterior joint capsules. These changes progressed rapidly until 6 weeks of immobilization and may advance slowly after 6 weeks. Joint contracture developed at the early stage of immobilization and progressed over time. The changes in the anterior and posterior joint capsules after joint immobilization may contribute to the limitation in flexion. The elevated mRNA expression of TGF-β1 may be related to joint capsule fibrosis and may be one of the causes of joint contracture.
Keywords: joint contracture; animal model; joint range of motion; joint capsule; rabbit